Natural arsenic in groundwater: occurrence, remediation and Management - Bundschuh, Jochen | Bhattacharya, Prosun (A. A Balkema Publishers / New York, 2005)
Arsenic contamination has become a global phenomenon. With the development of advanced technological detection toolts, more geographical areas seem to be affected by this probelm than envisaged before.